Compassion fatigue : coping with secondary traumatic stress disorder in those who treat the traumatized - Figley, Charles R.. (New York : Brunner/Mazel : Routledge, 1995)
"Compassion Fatigue focuses on those individuals who provide therapy to victims of PTSD - crisis and trauma counselors, Red Cross workers, nurses, doctors, and other caregivers who themselves often become victim to secondary traumatic stress disorder (STSD) or "compassion fatigue" as a result of helping or wanting to help a traumatized person." "Edited by Charles R. Figley, a renowned pioneer in the field of traumatic stress studies, this book consists of eleven chapters, each written by a different specialist in the field. It addresses such questions as: What are compassion stress and compassion fatigue? What are the unintended, and often unexpected, deleterious effects of providing help to traumatized people? What are some examples of cases in which individuals were traumatized by helping, and how were they traumatized? What are the characteristics of the traumatized caregiver (e.g., race, gender, ethnicity, age, interpersonal competence, experience with psychological trauma) that account for the development, sustenance, preventability, and treatability of secondary traumatization? Is there a way to theoretically account for all these factors? What are the characteristics of effective programs to prevent or ameliorate compassion stress and its unwanted consequences?"--Jacket.
Compassion fatigue as secondary traumatic stress disorder: an overview / Charles R. Figley -- Survival strategies: a framework for understanding secondary traumatic stress and coping in helpers / Paul Valent -- Working with people in crisis: research implications / Randal D. Beaton and Shirley A. Murphy -- Working with people with PTSD: research implications / Mary Ann Dutton and Francine L. Rubinstein -- Sensory-based therapy for crisis counselors / Chrys J. Harris -- Debriefing and treating emergency workers / Susan L. McCammon and E. Jackson Allison, Jr. -- Treating the "Heroic Healers" / Mary S. Cerney -- Treating therapists with vicarious traumatization and secondary traumatic stress disorders / Laurie Ann Pearlman and Karen W. Saakvitne -- Preventing secondary traumatic stress disorder / Janet Yassen -- Preventing compassion fatigue: a team model / James F. Munroe, Jonathan Shay, Lisa Fisher, Christine Makary, Kathryn Rapperport, and Rose Zimering -- Preventing institutional secondary traumatic stress disorder / Don Catherall -- Epilogue: The transmission of trauma.
Includes bibliographical references and indexes.
EBSCOhost.
Print version record.
Keywords: Secondary traumatic stress -- Treatment; Psychotherapists -- Job stress; Emergency medical personnel -- Job stress; Counselors -- Job stress; HEALTH & FITNESS -- Diseases -- General; MEDICAL -- Clinical Medicine; MEDICAL -- Diseases; MEDICAL -- Evidence-Based Medicine; MEDICAL -- Internal Medicine; Posttraumatische stressstoornis; Hulpverleners; Beroepsstress; Mitarbeiter; Psychotherapeut; Stress; Ärztlicher Notdienst; Aufsatzsammlung; Counselors -- Job stress; Emergency medical personnel -- Job stress; Psychotherapists -- Job stress; Stress Disorders, Post-Traumatic -- prevention & control; Stress Disorders, Post-Traumatic -- therapy; Empathy; Mitarbeiter; Psychotherapeut; Stress; Ärztlicher Notdienst; Ärztlicher Notdienst; Mitarbeiter; Stress; Aufsatzsammlung; Psychotherapeut